Estimation of wind energy production in relation to orographic complexity - A reliability study of two conventional computer software - Nilsson, Karl (My University, 2010)
The aim with this thesis is to compare two wind simulation software to simulate energy production which are based on two different flow models; a linear and a non-linear. The test parameter is orographic complexity and the test software is WAsP, which is based on the linear model and WindSim, which is based on the non-linear model. The test sites are N¨asudden and Hunnflen which have low orographic complexity and high orographic complexity respectively. At each site turbines with a long record of production are selected. In a first step the basics of wind approximations, measurements and conversion is presented. The aim with this is to present the input data for the flow models but also to show how complex winds, and thus wind simulations, are. Thereafter, the flow models are presented briefly. The simulation is performed by a preparation process in a third software called WindPRO and is followed by the actual simulations in the two simulation software. The results are then compared to measured production data of the chosen wind turbines. The results indicate that WAsP and WindSim estimate the energy production at a similar level which is close to the measured production when the orographic complexity is low. The WindSim simulation is very time consuming when comparing it to the WAsP simulation. When it comes to high orographic complexity the results indicate that WindSim estimates the energy production in a very close range to the measured production. The WAsP simulation, however, overestimates the energy production with about 40%. In the case with high orographic complexity the results show that a flow model that can calculate turbulence is needed. The model used in WindSim can model turbulence and therefore estimates an accurate energy production.
Keywords: Elkraftteknik; Electric power engineering